Analisis Penyebab dan Strategi Pencegahan Perilaku Menyontek pada Siswa/i di SMP Negeri 35 Medan - Ameliya Harahap; Asianna Manik; Delila Maya Sari Siregar; Lora Ernanta Tarigan; Nabila Amanda Pulungan; Shelly Elprida Gajah Manik (Journal Innovation In Education, 2024)
This research aims to find out the causes and strategies for preventing cheating among students at SMP Negeri 35 Medan. This research uses qualitative research methods using books and journals as additional references. This research was conducted by SMP N 35 Pecut Sei Tuan, North Sumatra. The results of the research show that cheating behavior still often occurs among students at SMP Negeri 35 Medan. This is motivated by the lack of concern from teachers, schools and parents regarding learning problems, especially cheating behavior, and also because there is pressure on students to get good grades. Thus, it has a negative impact on students' academic and moral development. Therefore, it is necessary to carry out various strategies including group guidance, and collaboration with subject teachers and homeroom teachers, individual guidance, and learning counseling in reducing students' cheating behavior at school.